The development of intercultural communicative competence of future translators studying german after english - Kurochkina, Elena (2021)
The purpose of this paper is to develop a methodology for the improvement of intercultural communicative competence for future translators studying German after English. The paper analyzes modern European documents on language education where communicative competence is determined through its inextricable link with plurilingual and pluricultural competencies. The authors propose methods for the formation of intercultural competence and clarify the goals of intercultural training of future translators. The paper concludes that in the practice of teaching German after English, one should adhere to the principles of learning a second foreign language based on materials that reflect the cultural realities of the country of the target language; taking into account the experience of students’ interaction with native speakers; motivating students’ interest in learning German after English; stimulating cognitive activity through solving conceptional and communicative tasks that simulate intercultural communication; using professionally-oriented assignments.